Pinna nobilis in suboptimal environments are more tolerant to disease but more vulnerable to severe weather phenomena. (January 2021) - Prado, Patricia; Grau, Amalia; Catanese, Gaetano; Cabanes, Pep; Carella, Francesca; Fernández-Tejedor, Margarita; Andree, Karl B.; Añón, Teresa; Hernandis, Sebastián; Tena, José; García-March, José Rafael
Abstract: We examined a disease outbreak of the fan mussel, Pinna nobilis (L.), in the Alfacs Bay (South Ebro Delta, Spain) during a period of two years in three zones exposed to a summer salinity gradient resulting from agricultural freshwater discharges and distance to the open sea. Long-term monitoring was also conducted in Fangar Bay (North Ebro Delta), featuring lower salinities and no evidence of disease. Results showed that the salinity gradient of Alfacs Bay (37.4–35.7) was associated to cumulative mortality (100% near the mouth, 43% in middle regions, and 13% in inner regions), thus hindering the spread of pathogens. Young specimens showed to be more tolerant to disease than large adults but become vulnerable over time. In Fangar Bay, lower salinities (30.5–33.5) prevented the disease but individuals were highly vulnerable to Storm Gloria which caused 60% mortality in 3 weeks, and ~100% in 6 weeks. Graphical abstract: Image 1 Highlights: Disease spread is relegating Pinna nobilis populations to lagoon-estuarine habitats. Pen shell mortalities were significantly associated to the salinity gradient. At summer salinities lower than 34 the disease was not detected. Populations in small-sized confined waters are highly vulnerable to storm events. Water management actions are possible at certain sites to prevent the disease.